Qualitative properties of structurally damped wave models - Matthes, Sascha; Reissig, Michael (Eurasian Mathematical Journal, 2013)
Qualitative properties such as precise decay estimates for energies of higher order and smoothing effects for a special class of structurally damped wave models are investigated in this paper. The main tools are diagonalization techniques and the theory of zones in the extended phase space. Some special effects for visco-elastic damped wave models are explained. These models are limit cases of structurally damped wave models interpolating between classical damped waves and visco-elastic waves.